1997
DOI: 10.1063/1.365563
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature detection of mobile impurities in compound semiconductors by transient ion drift

Abstract: We show that the transient ion drift (TID) method, which is based on recording junction capacitance under constant reverse bias [A. Zamouche, T. Heiser, and A. Mesli, Appl. Phys. Lett. 66, 631 (1995)], can be used not only for measurements of the diffusion coefficient of mobile impurities, but also to estimate the concentration of mobile species as part of the total dopant density. This is illustrated for CdTe, contaminated by Cu, and intentionally doped by Li or Ag and for CuInSe2. We show also that, with som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 26 publications
6
48
0
Order By: Relevance
“…Normalising the data to other lines in the PL spectrum yields similar results, but with a larger scatter of the extracted intensities. In accordance with the literature [3,14], the diffusion occurring during the annealing process resulted in a low concentration of 111 Ag, which is concluded from the low intensities of the Ag-related lines. They are not stronger than the lines related to the Li and Cu impurities, which are usually present in the order of 10 15 cm -3 .…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Normalising the data to other lines in the PL spectrum yields similar results, but with a larger scatter of the extracted intensities. In accordance with the literature [3,14], the diffusion occurring during the annealing process resulted in a low concentration of 111 Ag, which is concluded from the low intensities of the Ag-related lines. They are not stronger than the lines related to the Li and Cu impurities, which are usually present in the order of 10 15 cm -3 .…”
Section: Resultssupporting
confidence: 74%
“…In order to remove implantation-induced damage, the ZnTe crystals were annealed at 700 K for 30 min in a Te atmosphere and the CdTe crystals were annealed at 620 K in vacuum. Since Ag is a fast diffuser in both ZnTe and CdTe [3,14], the diffusion occurring during this annealing process resulted in a broad depth distribution and, as a consequence, in a low concentration of the 111 Ag atoms.…”
Section: Methodsmentioning
confidence: 99%
“…2(b) and 2(d) showed that a high V Cd concentration drastically reduces the diffusivity of Ag as is reflected by the large fraction of the Ag atoms remaining within a layer of about 20 m below the surface. Also the results for the undoped CdTe obtained by Lyubomirsky et al [15] and the p-type CdTe investigated by Kovalets et al [16] may be well understandable in view of the presence of a high and a low concentration of V Cd vacancies, respectively.…”
mentioning
confidence: 91%
“…There is evidence that Cu diffused from the ZnTe dopes the CdTe. It was shown that the Cu presence is essential not only for the small initial series resistance but also for the degradation (see sec.4.2) The Cu diffusion constant in single crystal CdTe is very high, about 3x10 -12 cm 2 /s [29] at room temperature. It is believed that the high diffusivity is due to the motion of interstitial Cu.…”
Section: Some Possible Effects Of Electromigration In Cdte Solar Cellsmentioning
confidence: 99%
“…According to [29] the diffusion coefficient of Cu, D Cu , in single crystal CdTe at T=300 K is about 3x10 C should be significantly higher, suggesting that the Cu concentration gradient in the CdTe adjacent to the ZnTe becomes small in a short time and no considerable additional diffusion of Cu into CdTe can take place in the following tens and hundreds of hours. Thus it is hard to expect a change in Cu concentration in the vicinity of the CdTe/ZnTe interface which can influence considerably the Schottky barrier properties.…”
Section: Influence Of Cu On Degradation Processmentioning
confidence: 99%